2018
DOI: 10.1371/journal.pone.0193864
|View full text |Cite
|
Sign up to set email alerts
|

‘More than a feeling’: An empirical investigation of hedonistic accounts of animal welfare

Abstract: Many scientists studying animal welfare appear to hold a hedonistic concept of welfare -whereby welfare is ultimately reducible to an animal’s subjective experience. The substantial advances in assessing animal’s subjective experience have enabled us to take a step back to consider whether such indicators are all one needs to know if one is interested in the welfare of an individual. To investigate this claim, we randomly assigned participants (n = 502) to read one of four vignettes describing a hypothetical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…We used a 2 x 2 factorial design varying natural living (pasture versus indoor housing) and affective state/biological functioning (experiencing versus not experiencing heat stress). Based upon the results of Robbins et al [ 12 ], we predicted that participants would express more positive attitudes towards pasture-based rearing even if this was associated with heat stress.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…We used a 2 x 2 factorial design varying natural living (pasture versus indoor housing) and affective state/biological functioning (experiencing versus not experiencing heat stress). Based upon the results of Robbins et al [ 12 ], we predicted that participants would express more positive attitudes towards pasture-based rearing even if this was associated with heat stress.…”
Section: Introductionmentioning
confidence: 98%
“…Expression of natural behavior was considered important by Flemish citizens, although not more so than the absence of disease [ 11 ]. One recent study used an experimental design to put naturalness and affective state concerns into conflict [ 12 ]. Participants were randomly assigned different scenarios describing “Sally” (a chimpanzee) as feeling either very good or very bad, and as living in either a naturalistic or a confined environment.…”
Section: Introductionmentioning
confidence: 99%
“…They are repelled by and concerned about practices they consider to be unnatural, such as the breeding of farm animals using artificial insemination [55] (p. 44) [57] (p. 30), and they oppose zero-grazing and cow-calf separation due to the loss of naturalness [54]. Furthermore, Robbins et al [58] found people generally prioritise naturalness over emotional states. They explain, "a chimpanzee living a natural life with negative emotions was rated as having better welfare than a chimpanzee living an unnatural life with positive emotions", and for "chimpanzees with positive emotions, those living a more natural life were rated as happier than those living an unnatural life" [58].…”
Section: Competing Conceptions Of Naturalnessmentioning
confidence: 99%
“…Furthermore, Robbins et al [58] found people generally prioritise naturalness over emotional states. They explain, "a chimpanzee living a natural life with negative emotions was rated as having better welfare than a chimpanzee living an unnatural life with positive emotions", and for "chimpanzees with positive emotions, those living a more natural life were rated as happier than those living an unnatural life" [58]. It appears that naturalness is a lens used by people when making assessments about what a good animal life is.…”
Section: Competing Conceptions Of Naturalnessmentioning
confidence: 99%
“…So one strain of empirical research that has developed in animal welfare science aims to uncover what the folk conception(s) of animal welfare is (are), in order to support or challenge some other conception of animal welfare. For example, Robbins, Franks, and von Keyserlingk () challenge the feelings conception of animal welfare by studying the folks' judgments about animal welfare in different scenarios where the animals differ on two dimensions: (a) positive and negative feeling and (b) the combined dimension of naturalness and health. The upshot is that the folk think that there is more to animal welfare than the feelings experienced by animals, so therefore, the feelings conception of animal welfare is empirically falsified…”
Section: Philosophical Issuesmentioning
confidence: 99%